Pengaruh Kinerja Lingkungan Dan Corporate Social Responsibility Terhadap Kinerja Keuangan - Fadillah, Muhamad Renaldi Razka; Rismayadi, Budi; Yanti, Yanti (Gorontalo Accounting Journal, 2024)
This study aims to examine the impact of environmental performance and Corporate Social Responsibility (CSR) on the financial performance of manufacturing companies in the basic and chemical sectors listed on the Indonesia Stock Exchange (IDX). The research adopts a quantitative methodology with a descriptive verification approach. Purposive sampling was employed to collect the data, which was then analyzed using SmartPLS software. The analysis includes testing the outer model, inner model, and hypothesis evaluation. The findings reveal that CSR has a significant effect on financial performance, whereas environmental performance does not show a significant impact. The study suggests further research to explore the influence of environmental costs and company size on financial performance, as well as expanding the sample to other industrial sectors.